Proceso de atención de enfermería en paciente de 28 años de edad con hipertiroidismo primario - Balladares Saltos, Kelly Ximena (2021)
The present clinical case is focused on a 28-year-old female patient who came to the emergency area due to diaphoresis, asthenia, asterixis and the presence of a palpable but not visible goiter (grade 1A). After the patient was stabilized, the vital constants were taken and assessed, where it was evidenced: Blood pressure: 130/78 mmhg, heart rate: 120bpm, respiratory rate: 20rpm, temperature: 36.5ºC and saturation of oxygen: 98%. Physician assesses and indicates corresponding laboratory tests. Especially TSH, T4, and HDL and a thyroid scan. Physical assessment was carried out using Marjorie Gordon's functional patterns in order to identify the dysfunctional patterns that compromised her state of health. Patient is transferred to hospitalization area I, for observation. Where the Nursing Care Process will be elaborated in order to develop a nursing care plan, using the Nanda, Nic and Noc taxonomies as essential tools, to fulfill the objective proposed in this clinical case study.